Analysis of the Influence of Bank Credit on Economic Growth in West Nusa Tenggara Province - Ahmadi, Sambirang; Basuki, Prayitno; Harsono, Iwan (The Es Economics and Entrepreneurship, 2024)
This research is motivated by the influence of banking credit on economic growth in NTB. The purpose is to analyze in depth the effect of bank lending consisting of investment loans, working capital loans and consumptive loans in NTB Province on the economic growth of NTB Province. The type of research used is descriptive quantitative. The type of data used in this study is time series data. The source of data used in this study is secondary data collected through documentation techniques, where data collection is done by studying some of the data contained in the archives, economic report documents, BPS NTB Province and Bank Indonesia from 2010 - 2023. Data analysis used is multiple linear regression. The results showed that investment credit and working capital credit partially had a positive and significant effect on economic growth in NTB, but consumptive credit showed that partially had no significant effect on economic growth in NTB. While simultaneously, the variables of investment credit, working capital credit and consumptive credit together have a positive and significant effect on economic growth in NTB.